E-cigarette, or vaping, product use Associated Lung Injury (EVALI): new scenarios for physicians and radiologists - Carmine Guarino (PAGEPress Publications, 2021)
A 59-year-old female ex-smoker with 40 pack year smoking history and a 5-year current e-cigarette (EC) use history, presented with progressive dyspnea on exertion and daily cough for 2 months. A CT scan showed a consolidation area with air bronchogram in the middle lobe and non-calcific bilateral nodules, which could be attributed to community-acquired pneumonia. The patient was treated with empiric antibiotics and systemic steroids for 10 days. Infectious, neoplastic and autoimmune pathologies were excluded, whereas a broncho-alveolar lavage revealed an accumulation of lipids in the cytoplasm of the alveolar macrophages. Despite the recommendation of vaping cessation, the patient continued to use EC. A new CT exam, carried out after 18 months, showed reversed halo sign (RHS), patchy ground-glass opacity (GGO), pleuro-parenchymal bands, and indeed perilobular pattern, suggestive of organizing pneumonia (OP). The final diagnosis was E-cigarette, or vaping, product use Associated Lung Injury (EVALI)- related OP.